RANCANG BANGUN ALAT TERAPI TEMPOROMANDIBULAR DISORDER MENGGUNAKAN METODE TRANSCUTANEOUS ELECTRICAL NERVES STIMULATION (TENS) BERBASIS TELEDENTISTRY TERINTEGRASI INTERNET OF THINGS (IoT) - Kusuma, Rizki Bagus Hadi; Nurussa’adah, n/a; Ambarwati, Rusmi (Jurnal Mahasiswa TEUB, 2025)
A disease characterized by craniofacial pain involving the joints, masticatory muscles, or muscles that innervate the head and neck is temporomandibular disorder (TMD). TMD is a major cause of pain in the orofacial region that is non-dental in nature. One of the factors causing TMD is hyperactivity of the muscles around the face. TMD often comes on suddenly, resulting in a decrease in the patient's quality of life, as it significantly interferes with the patient's ability to perform daily tasks such as eating, speaking, or yawning. An existing tool is Transcutaneous Electrical Nerve Stimulation (TENS) as one of the effective non-invasive, non-drug physical therapy techniques for the treatment of TMD. However, there are problems experienced at this time TENS has not been able to provide spontaneous and longterm therapy equipped with a monitoring application for the doctor in charge, so that its use remains under the supervision of a doctor. Through these problems, a technology is needed using the TENS method non-invasively accompanied by an Internet of Things (IoT) integrated doctor monitoring application. This innovation has been tested the functionality of the tool to determine the performance of the tool. In the output test, the percentage error and standard deviation of frequency 0.19% and 0.391 and voltage 0.075% and 0.1268 were obtained. TENS therapy testing results in a decrease in pain of 58%. The test results of internet data transmission of two different Access Point Bands with an average delivery time of 1.98 and 1.7 seconds.Keywords : temporomandibular disorder, TENS, Non-Invasive, Internet of Things